Digitalization of Islamic business: A narrative review - Fitri , Mulyana; Sirait, Frida Yanti; Sugianto, Sugianto (Universitas Islam Indonesia, 2023)
IntroductionDigitalization is an inevitable aspect of modern businesses. Without digitalization, businesses face challenges in the current era of Industry 4.0. However, studies regarding digitalization in Islamic or Sharia businesses are still limited.ObjectivesThis study intends to discuss digitalization in Islamic business, specifically in the Indonesian context. MethodThe method used in this study is a narrative review that analyzes literature related to Islamic business. A narrative review is used to provide a basic overview of the significance of digitalization in Islamic businesses.ResultsThe results show that digitalization can provide many benefits for businesses, including Islamic businesses. Islamic banks are one part of Islamic business, which is the first to digitize. Stakeholder support in Indonesia for the digitalization of Islamic businesses is adequate. ImplicationsIslamic businesses should begin digitalizing to maintain sustainability. Islamic business can emulate how Islamic banks have performed digitalization well.Originality/NoveltyThis study is unique in its analysis of the development of digitalization in Islamic businesses. This study is expected to spark further research in the field of Islamic business in Industry 4.0.